Digitalization and Efficiency: Technology-based Service of Indonesia Sharia Commercial Banks - Firsty Izzata Bella; M Fikri Himmawan (IQTISHADIA, 2021)
This study aims to assess the technology-based service effectiveness on bank profitability as well as to evaluate the efficiency and stability of Islamic Commercial Banks in Indonesia. The model was analyzed by using multiple linear regressions with generalized least square estimation technique and Data Envelopment Analysis (DEA) with data are gathered from Q1 2017 to Q2 2020. The exogenous variables included were Branchless Banking (BB), Third-party Funds (DPK), and Technology Service Quality (TSQ), with banking operational income (PENDOP) as endogenous variable. The DEA method analyses the VRS and CRS scale while using output orientation. Using the inputs of DPK, operational expenses, and total funding, with the outputs of operational earnings and total assets. The main finding suggests that DPK played as a dominant variable, following by TSQ and BB on bank operational income. Moreover, the results of the DEA models showed in four quadrants in each CRS and VRS model. Respectively, 1 and 5 banks are highly efficient and stable, 5 and 2 banks have high efficiency but low stability, 4 and 2 banks have low efficiency but high stability, 4 and 5 banks have low efficiency and stability in the CRS and VRS model.